O Homem Livre Sobre A Terra Livre: O Tipógrafo, O Jornalista Libertário E A Rede Social Do Jornal A Terra Livre (1905-1910) - Alvarenga, Lucas Thiago Rodarte [UNIFESP] (2017)
The Purpose Of This Paper Is To Analyze The Libertarian Anarchist Newspaper, A Terra Livre, Which Was Launched In São Paulo In 1905 And Circulated Until 1910. The Research Prioritizes The Newspaper In Its Conception, Structure And Forms Of Publication, As Well As The Performance Of Its Creators: Edgard Leuenroth And Neno Vasco, Journalists, Anarchists And Important Libertarian Militants Of The Time. This Analysis Seeks To Identify And Understand The Social Networks Formed By Journalists / Readers / Subscribers And Their Role As Contributors To The Circulation Of The Print And To Consolidate The Bases Of The Workers' Movement, As Well As To Analyze The Process Of Dispute Over Literary Culture In San Pablo And Carioca, Evidencing The Hegemonic Movements Of The Newspapers Of Great Circulation By The Circles Of Power In The Civil Society And By The Attempt Of The Working And Suburban Newspapers In Counterbalance These Games Of Power.